The MAP3K7 gene: Further delineation of clinical characteristics and genotype/phenotype correlations. Issue 10 (29th July 2022) - van Woerden, Geeske M.; Senden, Richelle; de Konink, Charlotte; Trezza, Rossella A.; Baban, Anwar; Bassetti, Jennifer A.; van Bever, Yolande; Bird, Lynne M.; van Bon, Bregje W.; Brooks, Alice S.; Guan, Qiaoning; Klee, Eric W.; et al.
Abstract: Mitogen‐activated protein 3 kinase 7 ( MAP3K7 ) encodes the ubiquitously expressed transforming growth factor β‐activated kinase 1, which plays a crucial role in many cellular processes. Mutationsin the MAP3K7 gene have been linked to two distinct disorders: frontometaphyseal dysplasia type 2 (FMD2) and cardiospondylocarpofacial syndrome (CSCF). The fact that different mutations can induce two distinct phenotypes suggests a phenotype/genotype correlation, but no side‐by‐side comparison has been done thus far to confirm this. Here, we significantly expand the cohort and the description of clinical phenotypes for patients with CSCF and FMD2 who carry mutations in MAP3K7 . Our findings support that in contrast to FMD2‐causing mutations, CSCF‐causing mutations in MAP3K7 have a loss‐of‐function effect. Additionally, patients with pathogenic mutations in MAP3K7 are at risk for (severe) cardiac disease, have symptoms associated with connective tissue disease, and we show overlap in clinical phenotypes of CSCF with Noonan syndrome (NS). Together, we confirm a molecular fingerprint of FMD2‐ versus CSCF‐causing MAP3K7 mutations and conclude that mutations in MAP3K7 should be considered in the differential diagnosis of patients with syndromic congenital cardiac defects and/or cardiomyopathy, syndromic connective tissue disorders, and in the differential diagnosis of NS.